Gait speed and malnutrition in hospitalized patients and the quality of life of their caregivers - Juliana Yukari Suganuma; Talita Yoshimura da Costa; Wanderson Roberto da Silva; Maria Claudia Bernardes Spexoto
ABSTRACT Objective: To verify the age, nutritional status, and gait speed in hospitalized individuals, and their association with the quality of life of their caregivers. Methods: Observational cross-sectional study with 54 patients and their respective caretakers in a university hospital in the Brazilian Midwest. The analyses were carried out using the SPSS software, with p < 0.05. Results: The Social Relations domain had the highest mean score (71.45±18.64). The lowest score was in the Physical domain (57.80±12.01). According to a subjective nutritional evaluation, 72.2% presented some degree of malnutrition. Most were classified with low gait speeds (82%). There was a significant correlation between age and the Physical and General Quality of Life domains. The Environment domain was significantly correlated to the gait speed. Conclusion: The age and the gait speed of the patient were related to the quality of life of the caregiver, but the nutritional state was not affected.